A Mechanism of Synaptic Clock Underlying Subjective Time Perception - Jura, Bartosz (Frontiers in Neuroscience, 2019)
Temporal resolution of visual information processing is thought to be an important factor in predator-prey interactions, shaped in the course of evolution by animals’ particular ecology. Here I show that light can be considered to have a dual role of a source of information, which guides motor actions, and an environmental feedback for those actions. I consequently show how temporal perception might depend on feedback-based behavioral adaptations realized in the nervous system through activity-dependent synaptic plasticity. I propose an underlying mechanism of synaptic clock, with every synapse having its characteristic time unit, determined by the persistence of memory traces of synaptic inputs, which is used by the synapse to tell time, and postulate the existence of a specific brain-wide distribution of synaptic clocks with different time units. The present theory offers a simple, testable link between the fields of neurobiology of memory, time perception and ecology, which may account for numerous experimental findings, including the interspecies variation in the temporal resolution and the properties of subjective time perception in humans, specifically the variable speed of perceived time passage, depending on emotional or attentional states or tasks performed.